First measurement of the quark-to-photon fragmentation function - BUSKULIC, D. (Institutional Knowledge at Singapore Management University, 1995)
Earlier measurements at LEP of isolated hard photons in hadronic Z decays, attributed to radiation from primary quark pairs, have been extended in the ALEPH experiment to include hard photon production inside hadron jets. Events are selected where all particles combine democratically to form hadron jets, one of which contains a photon with a fractional energy z 0:7. After statistical subtraction of non-prompt photons, the quark-to-photon fragmentation function, D(z), is extracted directly from the measured 2-jet rate. By taking into account the perturbative contributions to D(z) obtained from an O(S ) QCD calculation, the unknown non-perturbative component of D(z) is then determined at high z. Provided due account is taken of hadronization eects near z = 1, a good description of the other event topologies is then found.